1207 EXPLORING AUDIO-RECORDING IN TERMINAL ILLNESS - THE HOSPICE BIOGRAPHERS MODEL. (16th January 2023) - Halton-Hernandez, E; Ali, K; Cooney, G; Abrams, R
Abstract: Introduction: The therapeutic benefits of narrative in terminally ill patients is widely studied and evidenced in the research literature. The Hospice Biographers are a charity offering a professional free service for end-of-life patients the opportunity to audio-record their life story in a memory stick and to keep copies for themselves and for their families. The objective of this qualitative study is to explore the experience of a group of people either recording or listening to an audio-biography. Methods: Five semi-structured in-depth interviews with terminally ill adults who recorded an audio-biography and another interview with a family member were conducted virtually. Transcripts of the zoom interviews were coded using thematic analysis. Results: Our findings showed that patients found talking to a trained audio-biographer provided a neutral, non-judgemental interlocutor. The biographer helped them reminisce in a guided conversation navigating their life stories in chronological order. The experience of planning for the recording varied from preparing a mind-map, to writing down some guide notes or no preparation at all. Patients reported a feeling of catharsis while telling their stories as well as being able to reflect on and analyse significant life events. However, it was challenging to convey difficult emotions whilst being mindful of how patients' life stories might be perceived by families. Although there was a degree of uncertainty about impact of the recording upon listeners, it was felt that leaving a voice-recorded account would still be informative and beneficial. A personal narrative could also provide a wider historical account of the relevant time period. Some individuals fed back that they would have valued the opportunity to edit their recording after listening and include a visual element. Conclusions: Recording an audio-biography in terminal illness allows patients a space for reflection and provides a valued connection with immediate family members and future generations.